Glycogen synthase kinase-3β inhibition in the medial prefrontal cortex mediates paradoxical amphetamine action in a mouse model of ADHD - Yen, Yi-Chun; Gassen, Nils C.; Zellner, Andreas; Rein, Theo; Landgraf, Rainer; Wotjak, Carsten T.; Anderzhanova, Elmira (Frontiers in Behavioral Neuroscience, 2015)
Psychostimulants show therapeutic efficacy in the treatment of attention-deficit hyperactivity disorder (ADHD). It is generally assumed that they ameliorate ADHD symptoms via interfering with monoaminergic signaling. We combined behavioral pharmacology, neurochemistry and molecular analyses to identify mechanisms underlying the paradoxical calming effect of amphetamine in low trait anxiety behavior (LAB) mice, a novel multigenetic animal model of ADHD. Amphetamine (1 mg/kg) and methylphenidate (10 mg/kg) elicited similar dopamine and norepinephrine release in the medial prefrontal cortex (mPFC) and in the striatum of LAB mice. In contrast, amphetamine decreased, while methylphenidate increased locomotor activity. This argues against changes in dopamine and/or norepinephrine release as mediators of amphetamine paradoxical effects. Instead, the calming activity of amphetamine corresponded to the inhibition of glycogen synthase kinase3β (GSK3β) activity, specifically in the mPFC. Accordingly, not only systemic administration of the GSK3β inhibitor TDZD-8 (20 mg/kg), but also local microinjections of TDZD-8 and amphetamine into the mPFC, but not into the striatum, decreased locomotor activity in LAB mice. Amphetamine effects seem to depend on NMDA receptor signaling, since pre- or co-treatment with MK-801 (0.3 mg/kg) abolished the effects of amphetamine (1 mg/kg) on the locomotion and on the phosphorylation of GSK3β at the level of the mPFC. Taken together, the paradoxical calming effect of amphetamine in hyperactive LAB mice concurs with a decreased GSK3β activity in the mPFC. This effect appears to be independent of dopamine or norepinephrine release, but contingent on NMDA receptor signaling.